Degree of Conversion and Mechanical Properties of Resin Cements Cured Through Different All-Ceramic Systems - Lopes,Camila de Carvalho Almança (2015)
Abstract: The aim of this study was to verify the degree of conversion (DC), Vickers microhardness (VH) and elastic modulus (E) of resin cements cured through different ceramic systems. One 1.5-mm-thick disc of each ceramic system (feldspathic, lithium dissilicate and zircônia veneered with feldspathic) was used. Three dual-cured (Allcem, Variolink II and RelyX U200) and one chemically-cured (Multilink) resin cements were activated through ceramic discs. For dual-cured resin cements was used a conventional halogen light-curing unit (Optilux 501 at 650 mW/cm2 for 120 s). Samples cured without the ceramic disc were used as control. The samples were stored at 37 °C for 24 h. ATR/FTIR spectrometry was used to evaluate the extent of polymerization in the samples (n=5). Micromechanical properties - VH and E - of the resin cements (n=5) were measured with a dynamic indentation test. Data were statistically analyzed with two-way ANOVA, Tukey's test and Pearson's correlation (α=0.05). DC was affected only by the type of resin cement (p=0.001). For VH, significant interaction was detected between resin cement and ceramic (p=0.045). The dual-cured resin cements showed no significant differences in mean values for E and significantly higher values than the chemically-cured resin cement. The degree of conversion and the mechanical properties of the evaluated resin cements depend on their activation mode and the type of ceramics used in 1.5 mm thickness. The dual-cured resin cements performed better than the chemically-cured resin cement in all studied properties.